Transcranial Direct Current Stimulation in Treatment of Child Neuropsychiatric Disorders: Ethical Considerations - Auvichayapat, Narong; Auvichayapat, Paradee (Frontiers in Human Neuroscience, 2022)
Transcranial direct current stimulation (tDCS) is one of the noninvasive electrical stimulation which using a low electric current through two electrodes. The provided current passes from anode to cathode and induces electric fields in the surface neurons then modulates synaptic plasticity and finally changes cortical excitability or improves clinical outcomes which outlast after a duration of stimulation. Meta-analyses have supported the beneficial effects for tDCS treatments in child neuropsychiatric disorders. However, the study of vulnerable children is still controversial and it is a great deal for ethical considerations. Due to the developing brain has some importantly physiological difference from the matured brain i.e. less GABAergic inhibition and more myelination, therefore, the opportunity to modify neurological disorders to be close to normal level in childhood after tDCS is likely to be higher than in adults. On the contrary, these physiological differences may result in unexpectable excitability in children’s brain and was criticized to have an unsafe effect i.e. seizure, a serious adverse event. As mention above, using tDCS in children appear to be a double-edged sword and should be ethically considered prior to widely used. Assessing between benefits of tDCS treatment within the golden period of brain development and the risk of seizure provocation is important. Thus, this review aims to exhibit broad concepts about developing brain in overview, tDCS in children, pathophysiology of neuropsychiatric disorders and tDCS beneficence, tDCS safety and tolerability in children, and the debate issue “missing good opportunities or taking risks”